Penerapan Metode Pembiasaan dalam Membentuk Karakter Religius Anak Usia Dini di RAM NU 152 Wagir Lor Ngebel Ponorogo - Jumiah Nurhasanah; Samsudin (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The mentoring program for teachers aims to shape students' religious character through the implementation of habituation methods carried out by students of the Community Service Program (KPM) at RAM NU 152 Wagir Lor, Ngebel, Ponorogo. The method used is Asset-Based Community Development (ABCD), consisting of five stages: Discovery, Dream, Design, Define, and Destiny. The results show that students are able to demonstrate positive behaviors in developing their religious character, such as stronger spiritual connections with Allah SWT, patience, gratitude, obedience to parents, kind speech, and good manners. Although these changes are not yet significant, most students have shown improvements as described. Besides benefiting the students themselves, this program also provides valuable experience for KPM students in applying their academic skills in real-life settings. The collaborative approach among students, teachers, parents, and the local community fosters sustainable educational development by creating a positive and supportive learning environment. This indicates that the ABCD method approach in teacher mentoring activities has the potential to be replicated in other communities facing similar challenges in shaping students' religious character.